Wuzi Yanzong Pill—Based on Network Pharmacology and In Vivo Evidence—Protects Against Spermatogenesis Disorder via the Regulation of the Apoptosis Pathway - Chen, Wang-qiang; Ding, Cai-fei; Yu, Jia; Wang, Chen-ye; Wan, Ling-yi; Hu, Hui-min; Ma, Jian-xiong (Frontiers in Pharmacology, 2020)
Male infertility is in crisis as a human reproductive health-related issues worldwide. Wuzi Yanzong pill (WZYZP) is a traditional Chinese medicine prescription shows efficacy in kidney-reinforcement and essence-benefit to ameliorate male reproductive dysfunctions. However, the pharmacological mechanisms of WZYZP on male infertility have not been investigated and clarified clearly. This study was designed to investigate the effects of WZYZP on spermatogenesis disorder and explore its underlying pharmacological mechanisms. First, based on a network pharmacology study, 39 bioactive compounds and 40 targets of WZYZP associated with spermatogenesis disorder were obtained, forming a tight compound-target network. Molecular docking tests showed tight docking of these compounds with predicted targeted proteins. Protein-protein interaction (PPI) network identified TP53, TNF, AKT1, Bcl-XL, Bcl-2, and IκBA as hub targets. KEGG pathway network and pathway-target-compound network revealed that the apoptosis pathway was enriched by multiple signaling pathways and multiple targets including the hub targets. Subsequently, the chemical characterization of WZYZP was analyzed using UPLC-Q/TOF-MS, and 40 compounds in positive ion mode and 41 compounds in negative ion mode in WZYZP were identified. Furthermore, based on the prediction of network pharmacology study, a rat model of spermatogenesis disorder was established to evaluate the curative role and underlying mechanisms of WZYZP. The results showed that WZYZP treatment improved rat sperm quality and attenuated serum hormone levels, reversed histopathological damage of the testis, reduced cell apoptosis in testis tissues, and also ameliorated the expression of the predicted hub targets (TP53, TNF-α, AKT1, NFκB, and IκBA) and the apoptosis related proteins (Bcl-XL, Bcl-2, Bax, Caspase 3 and Caspase 9). These results indicated that WZYZP has a protective effect on spermatogenesis disorder, suggesting that it could be an alternative choice for male infertility therapy.